2008
DOI: 10.1111/j.1479-8301.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of behavioral and psychological symptoms of dementia in untreated oldest old Alzheimer's disease*

Abstract: Background: The proportion of the population aged 85 years and older has increased rapidly in Japan, reaching 2.5 million (1.99%) in 2002. Under these circumstances, the number of dementia patients increases annually. However, few studies have focused on Alzheimer's disease (AD) with an age at onset older than 85 years (oldest old AD). The aims of the present study were to determine the prevalence of the behavioral and psychological symptoms of dementia (BPSD) in patients with oldest old AD compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…Treatment of behavioral and psychological symptoms of dementia (BPSD) remains one of the most unmet needs in psychogeriatrics [7,8], with more effective pharmacological [9,10] and non-pharmacological interventions [11-13] needed. Psychogeriatrics is, however, a clinical subspecialty in which treatment should be directed towards the person as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of behavioral and psychological symptoms of dementia (BPSD) remains one of the most unmet needs in psychogeriatrics [7,8], with more effective pharmacological [9,10] and non-pharmacological interventions [11-13] needed. Psychogeriatrics is, however, a clinical subspecialty in which treatment should be directed towards the person as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the pathogenesis of BPSD is not yet fully understood, 1 clinicians are often expected to reduce the frequency and severity of BPSD by whatever means available; however, this is sometimes quite difficult. [2][3][4][5] Therefore, BPSD may increase the burden on patients' family and caregivers, and may be the main reason for visits to the hospital and/or clinic by patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…The Ser9Gly polymorphism of dopamine receptor D3 (DRD3) could disturb the membrane insertion of Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 7 this receptor molecule with biological consequence. Studies with FGA treatment response showed the Gly allele is more frequent among poor responders, however, recent studies with SGA showed a positive link of the Gly allele with a better response.…”
Section: Dopamine Receptor D3mentioning
confidence: 99%
“…The neurobiology of DISC1 in the normal developing and adult brain and its roles in SCZ are not well understood. The biological role of DISC1 is, however, speculated from the following findings: (i) downregulation of DISC1 accelerates morphological development of adult-born neurons resulting in soma hypertrophy and enhancement of dendritic outgrowth; (ii) inhibition of DISC1 leads to mispo-Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 9 sitioning of new neurons in the molecular layer from overextended migration, suggesting that DISC1 serves as an interpreter that relays positional signals to the intracellular migratory machinery rather than a direct mediator of neuronal migration; (iii) new neurons with DISC1 knockdown exhibit more mature neuronal firing patterns; and (iv) downregulation of DISC1 accelerates synapse formation of newborn neurons. Taken together, these results indicate that DISC1 controls the tempo of the entire process of neuronal integration in the adult brain as a master regulator.…”
Section: Disrupted In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation